Numerical Simulation of Smoke Control Effectiveness with Different Exhaust Modes in a Large Subway Station. (2018) - Zhou, Yang; Bu, Rong-wei; Xu, Zhi-sheng; Chen, Huo-ju; Gong, Jun-hui
Abstract: Fire smoke characteristics in the large subway transportation centre distinctly differ from others due to its complicated configuration and confined space. The smoke control effectiveness on different floors were studied with different smoke exhaust modes based on Shenzhen Che Kung Temple subway transportation centre by the method of large eddy simulation. The numerical simulation results show that high-temperature smoke is hard to gather due to the large space, and the effect of smoke control is obtained with different smoke exhaust and air supply modes. With the smoke exhaust volume specified by the relevant fire codes, the smoke spread in the basement can be effectively controlled, but the smoke movement in the sub-basement and third floor of underground are out of control. Meanwhile, some characteristic parameters such as smoke concentration, smoke temperature and visibility are effectively controlled by smoke exhaust and air supply of the entire region, and the smoke is better controlled in partial regions with smoke exhaust and air supply. Also, the smoke control effect in sub-basement is similar to that of third floor of underground.